Proceedings of the Sixth Workshop on Noisy User-Generated Text (W-Nut 2020) 2020
DOI: 10.18653/v1/2020.wnut-1.21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ASR on Alzheimer’s Disease Detection: All Errors are Equal, but Deletions are More Equal than Others

Abstract: Automatic Speech Recognition (ASR) is a critical component of any fully-automated speechbased dementia detection model. However, despite years of speech recognition research, little is known about the impact of ASR accuracy on dementia detection. In this paper, we experiment with controlled amounts of artificially generated ASR errors and investigate their influence on dementia detection. We find that deletion errors affect detection performance the most, due to their impact on the features of syntactic comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Cepstral Mel-Frequency Components (MFCC), among others [10]. Different combinations of these features were used in multiple previous studies when detecting AD from the speech collected via picture description tasks [4,5,11,12]. These works have provided clear evidence on the potential of using simple spoken tasks and conventional acoustic features to automatically assess early dementia and its progression as well as to demonstrate that technology allows automatic detection of AD.…”
Section: Extracting Conventional Acoustic Features From Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…Cepstral Mel-Frequency Components (MFCC), among others [10]. Different combinations of these features were used in multiple previous studies when detecting AD from the speech collected via picture description tasks [4,5,11,12]. These works have provided clear evidence on the potential of using simple spoken tasks and conventional acoustic features to automatically assess early dementia and its progression as well as to demonstrate that technology allows automatic detection of AD.…”
Section: Extracting Conventional Acoustic Features From Speechmentioning
confidence: 99%
“…This is not surprising, as conventional acoustic features were engineered based on substantial domain knowledge in the area of AD detection. Multiple previous studies [4,5,11,12] were using these features as the ones that characterize the speech of patients with AD the best.…”
Section: Generalizabilitymentioning
confidence: 99%
“…Linguistically-based features can be very informative to detect AD [16,17,18]; however, they rely on the performance of an ASR system, which are prone to introduce errors, or human transcriptions, which are very time-consuming, and they are language dependant. The more elaborate the language analysis is, more sensible to ASR errors will be, making a real system less robust.…”
Section: Alzheimer Disease Detection From Speechmentioning
confidence: 99%
“…There can be three types of language perturbations at the word level: insertions, deletions, and substitutions on words. (Balagopalan et al, 2019) showed that deletions are more affected (significantly) than insertions and substitutions, so we likewise focus on deletions. Following Balagopalan et al ( 2019), we artificially add deletion errors to original individual text samples at predefined levels of 20%, 40%, 60%, and 80%.…”
Section: Altering Text Samplesmentioning
confidence: 99%